Towards a professional learning framework for academics in a private higher education environment - Cronje, Franci (Stellenbosch : Stellenbosch University, 2017)
ENGLISH ABSTRACT : Within the context of re-positioning academic professional development as professional learning to place the focus on what the lecturer does, this research tries to understand professional learning practices in a particular South African private higher education environment. Research was conducted on four campuses of one higher education brand of The Independent Institute of Education. Relatively little has been written on academic professional development- and learning in the South African private higher education domain where the incentive of publishing with recognition and additional funding accompanied by such as in the public sphere, is lacking. This dissertation reports on two cycles of action research conducted on these four campuses, culminating in thematically analysed in-depth interviews with the four academic campus managers. Their reflections on professional learning progress on a year’s work conclude in finding that proper orientation and introductions can enhance staff cohesion while the role of academic campus managers as engineers of such cohesion and designing custom-made professional learning initiatives on a campus is pivotal. Academic campus managers should spend considerable time and effort on strategising their campus programme while leadership should be decentralised to afford academic campus managers more agency to lead the team. These academic campus managers should hold leeway to award more incentives to individual performers within their teams but that they should be held accountable for actions - or lack thereof, that did not culminate in successful practices. Academic campus managers should be considered a very valuable and unique resource. In order for the role of the academic campus manager to operate optimally, central leadership should take care to appoint the most appropriate person to fit this profile and to deem them directly accountable for the state of academic professional learning on their campus. Central management should also heed the need for resources such as opening up the possibilities of monetary- and other incentives, and open up the possibilities, thereby enabling academic campus managers to use these incentives at their discretion.